Reappraising legal, political and ethical questions concerning the Herero and Nama genocide - Böcker, Julia (Julia Franziska Maria) (Brill/Nijhoff, 2024)
""In the face of such 'unspeakable truths, ' wouldn't it be better to simply, quietly bow out?" (Kora Andrieu: Sorry for the Genocide, 2009). This book affirms this question regarding colonial crimes through an interdisciplinary approach. For coming to terms with massive systemic injustice, not only the historic foundations and legal questions are relevant, but also political viewpoints as well as peace ethics. The book reveals: In the face of extreme violence, even genocide, a political apology can be an effective tool for conflict transformation, even when the injustice is far in the past"-- Provided by publisher
Keywords: William -- II, -- German Emperor, -- 1859-1941.; Namibia -- History -- Herero Revolt, 1904-1907.; Namibia -- History -- Nama Revolt, 1904-1907.; Genocide -- Law and legislation -- Namibia -- 20th century.; Herero (African people) -- History.; Nama (African people) -- History.; Apologizing -- Social aspects.; Reparations for historical injustices.; Namibie -- Histoire -- 1904-1907 (Révolte des Herero); Excuses (Regret) -- Aspect social.; Réparations des crimes de l'histoire.; Herero (Peuple d'Afrique) -- Histoire.; Nama (Peuple d'Afrique) -- Histoire.